Cloud Platform Selection Model in the Framework of Differential Quality Game With Fuzzy Information - Kaiyrbek Makulov; Arkadii A. Chikrii; Valery Lakhno; Bagdat Yagaliyeva; Volodimir Malyukov; Inna Malyukova; Miroslav Lakhno (IEEE Access)
The paper presents a mathematical model integrated into the computational core of a decision support system (DSS) for the selection of cloud platforms under conditions of fuzzy information. The model facilitates the development of rational strategies for players’ interaction with cloud platforms, allowing to balance investment, security and quality of services provided. This study proposes a methodology for determining optimal strategies in cloud platform selection using a differential quality game under fuzzy conditions, taking into account their preferences and opportunities to use technologies related to the analysis of user activities, i.e., digital footprints. The performed computational experiments confirmed the effectiveness of the model and allowed us to visualize the results of the interaction based on synthetic data. The results of the study may be useful to analysts dealing with cloud solution selection problems under uncertainty and cybersecurity needs. The relevance of the study is due to the global trend of business processes moving to the cloud and the increasing requirements for data security in the digitalization of the economy, which makes the choice of an optimal cloud platform strategically significant. Employing a differential quality game with fuzzy information, this study introduces a reliable DSS that incorporates cost, security and QoS to select the most appropriate cloud platform. The computational experiments validate the model in reproducing plausible interactions yielding relevant insights for decision-makers.